2019
DOI: 10.1002/1348-9585.12025
|View full text |Cite
|
Sign up to set email alerts
|

Organizational response to workplace violence, and its association with depressive symptoms: A nationwide survey of 1966 Korean EMS providers

Abstract: Objectives This study investigated whether organizational responses modified the associations between experiencing violence and depressive symptoms among emergency workers. Methods A nationwide survey of 1966 Korean emergency medical service (EMS) providers was analyzed. Experience of workplace violence (ie, physical violence, verbal abuse) was classified into four groups based on the victims’ reporting and organizational responses: (i) “Not experienced,” (ii) “Experien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 30 publications
(54 reference statements)
1
18
0
1
Order By: Relevance
“…Similarly, a substantial part of the literature has found that workplace violence may increase the prevalence of anxiety and depression among healthcare workers. 17,[33][34][35] In the context of the COVID-19 outbreak, exposure to violence may further exacerbate the already unprecedented COVID-19-related stress and burnout that healthcare workers are experiencing. 13 Consequently, exposure to violence has detrimental effects on healthcare workers' mental health.…”
mentioning
confidence: 99%
“…Similarly, a substantial part of the literature has found that workplace violence may increase the prevalence of anxiety and depression among healthcare workers. 17,[33][34][35] In the context of the COVID-19 outbreak, exposure to violence may further exacerbate the already unprecedented COVID-19-related stress and burnout that healthcare workers are experiencing. 13 Consequently, exposure to violence has detrimental effects on healthcare workers' mental health.…”
mentioning
confidence: 99%
“…Therefore, working with suffering persons generates WPV since they are likely frustrated and irritated due to their illness and pain. It was found that suffering persons are impatient in the matter of waiting time as long as they are often expecting to receive punctual care [ 38 ]. Violence is common amongst healthcare workers in contact with them and it is frequently reflected as an unavoidable part of the occupation [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…It was found that suffering persons are impatient in the matter of waiting time as long as they are often expecting to receive punctual care [ 38 ]. Violence is common amongst healthcare workers in contact with them and it is frequently reflected as an unavoidable part of the occupation [ 38 ]. This is the case of the nurses giving emergency care, or working in accident and emergency and for nurses working with patients with HIV/AIDS.…”
Section: Discussionmentioning
confidence: 99%
“…The gender difference in underreporting hiring discrimination observed in this study could be public health concerns. Although previous studies have indicated that not disclosing a violent event to others can negatively influence the victims' health [41][42][43], few studies examine the underestimating the health impacts of discrimination due to under-reporting. As a posthoc analysis, we examined the association between hiring discrimination and self-rated health after dividing the response to hiring discrimination among the entire population into four…”
Section: E P U B a H E A D O F P R I N Tmentioning
confidence: 99%